Hypersensitivity to mosquito starting in winter. - Bonifazi, E.; Bellomo, G.; Mazzotta, F. (European Journal of Pediatric Dermatology, 2004)
Here are reported five cases of hypersensitivity to mosquito arisen for the first time in winter when mosquitoes are not biologically active. Notwithstanding, the history, the distribution of lesions and the prolonged observation of the clinical course confirmed the diagnosis of cutaneous hypersensitivity to mosquito. We hypothesize that antigenic residua of saliva persist for a more or less long period of time in the sites of sting and can be responsible for hypersensitivity reactions several months after the sting, when sensitization against these antigens occurs for the first time.